ANALISIS CURAHAN WAKTU KERJA WANITA PENGUSAHA AGROINDUSTRI MAKANAN SKALA RUMAH TANGGA DI KECAMATAN KUOK KABUPATEN KAMPAR - Satriati, Fujiastari; Khaswarina, Shorea; Maharani, Evy (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2015)
The purpose of this research is to analyze the working hours of women entrepreneurs agro industry food household in Sub-District Kuok of Regency Kampar. The sampling method in this research using census sampling technique by making a sample of the entire population. This research was conducted in District Kuok of Regency Kampar. The results of the analysis show the total working time productive activities of women entrepreneurs is 3.536,67 hours/month or 79%, total working time on reproductive activities is 854,17 hours/month or 19% and in social activities total working time is 110,00 hours/month or 2%. Based on the standard normal working hours there are 3 (21%) women entrepreneurs who have business hours according to standards, while 11 (79%) women entrepreneurs have standard working hours exceeding normal working hours. Keywords : Working hours of women, productive activities, reproductive activities, social activities